Differential migration prospects, skill formation, and welfare - Oded Stark; Roman Zakharenko (University of Bonn, Center for Development Research (ZEF), 2011)
This paper develops a one sector, two-input model with endogenous human capital formation. The two inputs are two types of skilled labor: engineering, which exerts a positive externality on total factor productivity, and law, which does not. The paper shows that a marginal prospect of migration by engineers increases human capital accumulation of both types of workers (engineers and lawyers), and also the number of engineers who remain in the country. These two effects are socially desirable, since they move the economy from the (inefficient) free-market equilibrium towards the social optimum. The paper also shows that if the externality effect of engineering is sufficiently powerful, everyone will be better off as a consequence of the said prospect of migration, including the engineers who lose the migration lottery, and even the individuals who practice law.
Keywords: F22; J61; R23; 330; Heterogeneous human capital; Differential externality effects; Migration of educated workers; Human capital formation; Efficient acquisition of human capital; Beneficial brain drain; Einwanderung; Internationale Wanderung; Humankapital; Qualifikation; Brain Drain; Externer Effekt; Wohlfahrtsanalyse; Theorie